Cross‐cultural prevalence of sleep quality and psychological distress in healthcare workers during COVID‐19 pandemic. Issue 11 (17th October 2021) - Khan, Hamza Rafique; Ashraf, Farzana; Ullah, Irfan; Tahir, Muhammad Junaid; Dominari, Asimina; Shoib, Sheikh; Naeem, Hamna; Reddy, Gowry; Mukherjee, Pramit; Akram, Ifrah; Kamada, Sudha; Memon, Roshni Riaz; et al.
Abstract: Background: Poor quality sleep and emotional disturbances are expected in times of crisis. COVID‐19 has severely impacted healthcare worldwide and with that comes the concern about its effects on healthcare workers. The purpose of the present study was to assess sleep quality and psychological distress in healthcare workers during the COVID‐19 pandemic. Methods: The present work is a multi‐centric cross‐sectional study targeting healthcare workers from India, Pakistan, and Nepal. It used an online version of the Pittsburg Sleep Quality Index and the General Health Questionnaire, and data were analyzed using SPSS V.24. Results: A total of 1790 participants completed the questionnaire. Of the 1790 participants, 57% reported poor sleep quality, and 10% reported a high level of psychological distress. A cross‐cultural comparison found some differences between the different groups of participants. The details of the differences were further explored in the article. Conclusion: The present study highlights that a significant proportion of healthcare workers are affected by poor sleep quality and psychological distress during the COVID‐19 pandemic. It also emphasizes the imperative to provide them with psychosocial support to avoid potential short‐ and long‐term psychological consequences of these troubling times. Abstract : The present study highlights that a significant proportion of healthcare workers are affected by poor sleep quality and psychological distress during the COVID‐19 pandemic. It also emphasizes the imperative to provide them with psychosocial support to avoid potential short‐ and long‐term psychological consequences of these troubling times.